Determinación de los costos de producción del cultivo orgánicos de la uvilla (Physalis peruviana L.) en la asociación de producción agrícola HORTAVEL Manzano Guarangui, parroquia el Sagrario - Ibarra - Guamán Pizanàn, Miguel Ángel (2019)
SUMMARY The present study leads to an analysis of organic uvilla production in the high communities of the parish of El Sagrario del Cantón Ibarra for this identification was worked with the Association of farmers HORTAVEL. M.G. from the Manzano Guarangui community which is made up of 20 active members of which 19 partners have uvilla cultivation in orchards from 1000 m to one hectare depending on the availability of the resource as observed in the results of the survey is controlling diseases and pests with green seal products and with plant extracts mixed with an adherent when it is made milk, molasses or soap, the control is effective if it is applied immediately when diagnosing the pest or disease in the same way the fertilization of culture is performed with biol and organic fertilizer which allows to make less use of agrochemicals either for its chemical value or for its contaminating effect for the health of the people who consume the fruit of uvilla. The price when traders or buyers of uvilla see that it is organic increases in a percentage what has allowed to obtain better income. It is important to work on the scheduling of the crops based on the phenological phases so as not to have certain production dates. Keyword: uvilla, organic, biol, extract, chili, garlic, uvilla costs